Miles ahead [videorecording (DVD)] - Cheadle, Don; Cheadle, Don; Corinealdi, Emayatzy, 1980-; McGregor, Ewan, 1971- (Sony Pictures Home Entertainment, 2016)
In the midst of a dazzling and prolific career at the forefront of modern jazz innovation, Miles Davis disappears from public view for a period of five years in the late 1970s. Alone and holed up in his home, he is beset by chronic pain from a deteriorating hip, his musical voice stifled and numbed by drugs and medications, and his mind haunted my unsettling ghosts from the past.